High cytotoxicity of a degraded TBBPA, dibromobisphenol A, through apoptotic and necrosis pathways. Issue 1 (January 2023) - Suyama, Keitaro; Kesamaru, Hitoshi; Okubo, Takashi; Kasatani, Kazumi; Tomohara, Keisuke; Matsushima, Ayami; Nose, Takeru
Abstract: Halogenated flame retardants comprising bisphenol A (BPA) derivatives, such as tetrabromobisphenol A (TBBPA), have been studied their adverse effects on human health. However, despite the fact that these halogenated BPAs are easily degraded in the environment, the risks to living organisms due to these degraded products have mostly been overlooked. To evaluate the potential toxicity of degraded TBBPAs and related compounds, we examined the cytotoxicity of halogenated bisphenol A derivatives possessing one to four halogen atoms in vitro . The results indicated that the degraded TBBPA derivatives exhibited strong cytotoxicity against HeLa cells than TBBPA. Interestingly, the di-halogenated BPA derivatives possessing two halogen atoms exhibited the strongest cytotoxicity among tested compounds. In addition, a lactate dehydrogenase release assay, fluorescence spectroscopy and flow cytometry results indicated that dibromo-BPA and diiodo-BPA induced both apoptotic and necrotic cell death by damaging the cell membranes of HeLa cells. Moreover, Escherichia coli growth was inhibited in the presence of dehalogenated TBBPA and related compounds. These findings suggest that halogenated BPA derivatives that leak from various flame-retardant-containing products require strict monitoring, as not only TBBPA but also its degraded products in environment can exert adverse effects to human health. Graphical abstract: Image 1